Using Mindfulness Techniques to Improve Student Wellbeing and Academic Performance for University Students: A Pilot Study - Monika Goretzki; Ania Zysk (JANZSSA)
This paper examines the effectiveness of a three week mindfulness group program as a tool for improving academic performance, managing study stress and improving overall well-being. A mindfulness based approach was chosen due to its effectiveness in reducing stress as well as improving psychological wellbeing and working memory in various groups of university students. Evaluations from students over a three year period have consistently reported improved life and study skills across a number of areas, including capacity to manage stress and to stay more present. They also reported increased focus and improved sleep. The outcomes demonstrate an effective and innovative way to support student learning and wellbeing as well as providing students with a non-threatening way to engage with the counselling service.